Inisiasi Optimalisasi Fungsi Perencanaan Head Nurse dalam Pengelolaan Linen - Rahma Jumila; Hanny Handiyani; Dewi Gayatri; Masfuri Masfuri; Ati Surya Mediawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study report aims to identify planned changes in the initiation of optimization of the planning function in Linen Management. This method uses a case study approach using interviews, document review and observation, and Ishikawa's analysis. the results of the study shared that the application of the planning function in linen handling had not been optimal, as a result it had an impact on nursing services in the room. The management of linen in the room does not yet have standard guidelines and regulations for managing linen in each room. In conclusion, optimizing the planning function of the Head Nurse in linen management through drafting guidelines for linen management, the leadership's efforts to strengthen and sustain changes can be made by ratifying linen management regulations.Keywords: planning function, service quality, linen management, planned change.